2008
DOI: 10.2353/ajpath.2008.080237
|View full text |Cite
|
Sign up to set email alerts
|

Thrombospondin-1 and CD47 Limit Cell and Tissue Survival of Radiation Injury

Abstract: Radiation, a primary mode of cancer therapy, acutely damages cellular macromolecules and DNA and elicits stress responses that lead to cell death. The known cytoprotective activity of nitric oxide (NO) is blocked by thrombospondin-1, a potent antagonist of NO/ cGMP signaling in ischemic soft tissues, suggesting that thrombospondin-1 signaling via its receptor CD47 could correspondingly increase radiosensitivity. We show here that soft tissues in thrombospondin-1-null mice are remarkably resistant to radiation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
73
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 76 publications
(81 citation statements)
references
References 45 publications
7
73
1
Order By: Relevance
“…1). Consistent with these reports, we have found that TSP1 and CD47 null vascular cells and tissues do not undergo cell death in response to high-dose radiation (44). CD47-mediated cell and tissue death under radiation stress appears to occur in part by activation of apoptosis.…”
Section: Activated Cd47 Stimulates Multiple Cell Injury Pathwayssupporting
confidence: 78%
See 1 more Smart Citation
“…1). Consistent with these reports, we have found that TSP1 and CD47 null vascular cells and tissues do not undergo cell death in response to high-dose radiation (44). CD47-mediated cell and tissue death under radiation stress appears to occur in part by activation of apoptosis.…”
Section: Activated Cd47 Stimulates Multiple Cell Injury Pathwayssupporting
confidence: 78%
“…TSP1 is the only known soluble high-affinity ligand for the ubiquitous cell receptor CD47 (40), although signal regulatory protein-␣ (SIRP-␣) functions on phagocytes as a counterreceptor to CD47 (94). New findings identify CD47 as a regulator of multiple cell survival and cell death pathways (44,46,85), suggesting an important role for the TSP1-CD47 axis in renal injury.…”
mentioning
confidence: 99%
“…Similarly, we recently showed that TSP2-null mice do not replicate the radioresistance phenotypes of TSP1-and CD47-null mice (47).…”
Section: Discussionmentioning
confidence: 87%
“…1,2 Lack of CD47 in the JinB8 clone of Jurkat T cells (CD47 − ) similarly conferred resistance to increasing doses of ionizing radiation as assessed by cell viability 72 h after exposure (Fig. 1A).…”
Section: Deficiency Of Cd47 Increases Radioprotection Of Jurkat T Cellsmentioning
confidence: 99%
“…4 Agonists of this pathway such as THBS1 inhibit tumor growth and angiogenesis, but antagonists improve tissue survival of ischemic insults and radiation injuries. 2,[5][6][7] Deficiency of CD47 or THBS1 or suppression of CD47 results in radioprotection of human endothelial cells in vitro and protects soft tissue and bone marrow in vivo. 1 Moreover, suppression of CD47 in combination with IR enhances the IR-induced delay of tumor regrowth for syngeneic melanoma and squamous carcinoma models.…”
Section: Cd47 Deficiency Confers Cell and Tissue Radioprotection By Amentioning
confidence: 99%